Basics of design - Graham, Lisa (Thomson/Delmar Learning, 2005)
Its uniquely conversational tone - combined with numerous "before" and "after" illustrations- provides everything needed to design pages as effective as those of professional designers. Part One introduces readers to important design principles, as well as how to use color and images to add impact to designs. Part Two concentrates on the basics of typography. Part Three features a number of common design projects of the variety frequently assigned to non-designers (.., company business cards, fax cover letters, graphical and statistical reports, and more). To further aid readers, each project is accompanied by a brief listing of some of the special considerations involved in that type of visual page design. The final chapter of the book lists useful design books and resources for readers interested in advancing their typography and layout skills